Arsitektur Eco-Friendly pada Perancangan Pasar Tradisional di Kota Medan - Shafira Imanina; Wahyuni Zahrah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Traditional markets are places where sellers and buyers interact directly in social and economic aspects. This design aims to create cleanliness and comfort for visitors by using an eco-friendly architectural approach. This study's research method uses qualitative methods through literature studies and also field observations with primary data obtained through surveys, documentation and interviews. Then carry out an analysis of the site and architectural aspects to serve as guidelines for design. This design implements the main concepts, including zoning which consists of a public zone, namely the traders' room, inner court, food court area, event area and parking area, a semi-public zone, namely the reception room in the management room, a private zone, namely the management room and service zones, namely security post, loading dock, toilet, prayer room and service room. The zoning concept is based on its function, namely a traditional market where the parking area surrounds the market building, then there is a loading dock area that surrounds the market building and there is a food court area in the inner court of the market and an event area in the market section. This market building has an open concept which only has a roof as protection from sunlight and rain. This building has a height of 1 floor with a spatial arrangement for wet commodities and dry commodities and also non-food items in the front area. The central part of the room or the center of the room has an inner court area for culinary delights by adding a concept and having lighting that comes from skylights on the roof.